BANKRUPTCY PREDICTION ANALYSIS USING GROVER METHODS, SPRINGATE, ZMIJEWSKI SUB SECTOR HOTEL, RESTAURANT, TOURISM IMPACT OF THE COVID-19 PANDEMIC - Reny Febiani; Dede Hertina (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2022)
This study aims to: (1) analyze bankruptcy predictions using the grover, springate and zmijewski methods in the hotel, restaurant and tourism sub-sectors listed on the Indonesia Stock Exchange as the impact of the 2020-2021 Covid-19 pandemic, (2) analyze the differences between the methods Grover, Springate, and Zmijewski in predicting bankruptcy. The population of this study was 35 companies with a sample of 28 companies. The research method used in this study is quantitative with a descriptive approach and performs a non-parametric test using the Kruskal Wallis test to find differences between the three methods used. The results of the Kruskal Wallis test showed that there was a significant difference between the grover, springate and zmijewski methods in predicting bankruptcy and the most accurate method was the zmijewski method with an accuracy rate of 85.72% and an error of 14.28%.